The Biosphere and Civilization: In the Throes of a Global Crisis - Danilov-Danil'yan, Victor I. (Springer International Publishing, 2018)
This book attempts to explain the dire ecological, social, and economic situations facing mankind through simple, yet comprehensive analyses of global ecological issues, poverty, environmental stability and regulation, and sustainable development. The book conveys complex objects of study, namely the biosphere and the dire anthropogenic processes it has been experiencing for decades, so that the work is accessible without omitting key components of the subject matter. Readers will learn about the crises facing our global civilization (many of which originate from human causes yet cannot be solved by human technologies), the social and economic contributors to a threatened biosphere, the potential solutions to these problems, the mechanisms that maintain the stability of the global environment, and the scales at which sustainable development and preservation can be applied to initiate environmental regulation. Though intended to appeal to the general public and non-specialists, environmental researchers, organizations involved in sustainable development and conservation, and students engaged in ecology environment, and sustainability studies will also find this book of interest.